1972
DOI: 10.1149/1.2404387
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Reactions with Consecutive Charge-Transfer Steps: Steady-State and Time-Dependent Behavior under Charge-Transfer and Diffusion Control

Abstract: Electrochemical reactions involving consecutive charge‐transfer steps as expressed by the reaction schema Sv=Sv+1+zve− v=1,2,…,n are considered assuming that the only irreversible processes are charge‐transfer and diffusion and that disproportionation of the intermediate reaction products does not occur. An arbitrary number of n consecutive steps is assumed where feasible, but detailed discussion is restricted to the experimentally best understood case of a two‐step reaction. A general description is given of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1972
1972
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Thus, it has been shown that, with the appropriate normalization in each case, the electrochemical signal obtained when normal pulse voltammetry (NPV) is applied in the case of solution soluble species for electrodes of any geometry and size is coincident with the charge transferred-potential one for surface-confined systems in any electrochemical technique. Thus, their derivatives lead to a common normalized peak-shaped voltagram in derivative normal pulse voltammetry (dNPV), for solution soluble molecules, ,,, and in cyclic voltammetry (CV), for surface-immobilized ones. ,, , These normalized responses are only potential-dependent as a consequence of the reversible behavior of the process, which is reflected in the independence of time of surface concentrations (solution phase case) , and excesses (immobilized species). …”
Section: Introductionmentioning
confidence: 99%
“…Thus, it has been shown that, with the appropriate normalization in each case, the electrochemical signal obtained when normal pulse voltammetry (NPV) is applied in the case of solution soluble species for electrodes of any geometry and size is coincident with the charge transferred-potential one for surface-confined systems in any electrochemical technique. Thus, their derivatives lead to a common normalized peak-shaped voltagram in derivative normal pulse voltammetry (dNPV), for solution soluble molecules, ,,, and in cyclic voltammetry (CV), for surface-immobilized ones. ,, , These normalized responses are only potential-dependent as a consequence of the reversible behavior of the process, which is reflected in the independence of time of surface concentrations (solution phase case) , and excesses (immobilized species). …”
Section: Introductionmentioning
confidence: 99%